2015
DOI: 10.1186/s12909-015-0438-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality and impact of appraisal for revalidation: the perceptions of London’s responsible officers and their appraisers

Abstract: BackgroundTo evaluate NHS England London region’s approach to the revalidation appraisal of responsible officers in London, exploring perceptions of the quality and impact of the appraisal process. Revalidation is the process which aims to ensure doctors in the UK are up-to-date and fit to practice medicine thus improving the quality of patient care. Revalidation recommendations are largely premised on the documentation included in annual appraisals, which includes the professional development a doctor has und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The skills of the appraiser (context) were reported as being crucial to an effective appraisal . The success of appraisal partially depends on the quality of the feedback provided by the appraiser .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The skills of the appraiser (context) were reported as being crucial to an effective appraisal . The success of appraisal partially depends on the quality of the feedback provided by the appraiser .…”
Section: Resultsmentioning
confidence: 99%
“…The skills of the appraiser (context) were reported as being crucial to an effective appraisal. 14,33,34,[47][48][49][50][51][52] The success of appraisal partially depends on the quality of the feedback provided by the appraiser. 50 Thus if the appraiser is highly skilled (context) and able to effectively deliver feedback (context), this triggers the dissonance mechanism, which is more likely to lead to the appraisee developing insight (outcome).…”
Section: Dissonancementioning
confidence: 99%
“…Written reflection was often brief and lacking in detail and interview data suggested that many doctors would rather reflect verbally, either at the time with colleagues or with their appraiser in the appraisal meeting, a finding backed up by the wider literature. 1,6,26,27 For their part, appraisers wanted doctors to be selective in the documents they chose to include in their portfolios and would prefer to see a few examples of high quality reflection rather than many documents submitted somewhat indiscriminately and with no commentary on their impact or meaning for a doctor's practice. There are already moves to support a focus on quality over quantity when submitting supporting information.…”
Section: Discussionmentioning
confidence: 99%
“…If so, revalidation cannot only be dehumanizing, but also misses an opportunity to address problems. This would be a manifestation of the dehumanizing potential of rational systems, when paradoxically there is evidence that to achieve desired behavioral change it is the very nature of 'the personal' within appraisals, two people coming together to reflect on data, that helps to accomplish positive action (41,42).…”
Section: Discussionmentioning
confidence: 99%